Use of a carbonated beverage to disintegrate a phytobezoar obstructing the intrathoracic portion of the oesophagus of a horse. (4th April 2019) - Livesey, L. C.; Yorke, E.; Parra, A.; Gray, Q.; Davies, C.; Weldon, D.; Schumacher, J.; Kimura, S.; Howard, C.; Sierra‐Rodriguez, T.; Mora‐Pereira, M.
Summary: This report describes the treatment of a 17‐year‐old American Quarter Horse gelding for an oesophageal obstruction of approximately 24 h' duration. An intraluminal oesophageal mass resembling a phytobezoar and located close to the cardia, was observed during endoscopic examination of the oesophagus of a horse showing signs of oesophageal obstruction. An intrathoracic oesophageal diverticulum, filled with fluid, was observed about 40 cm proximal to the obstruction. The end of a nasogastric tube was guided beyond the diverticulum, using gastroscopic observation, so that its tip rested close to the obstruction. The obstruction failed to disintegrate or move into the stomach despite vigorous, prolonged lavage. With the nasogastric tube left in place, and the horse's head elevated, 0.5 L cola was administered adjacent to the obstruction through the nasogastric tube. The head was maintained in the elevated position for an hour, after which time the head was lowered and oesophageal lavage resumed. The nasogastric tube was passed into the stomach within 3 min of re‐instituting lavage. The successful use of a carbonated beverage to treat human patients for oesophageal or gastrointestinal obstruction caused by a phytobezoar is well documented. Carbonated beverages have also been reported to be effective in treating horses for gastric and enteric impactions caused by persimmon seeds. Administering cola into the oesophagus may help resolve oesophageal obstruction of horses caused by a phytobezoar or impacted feed material when horses are refractory to other treatments.